Efektifitas E-Learning Madrasah dalam Pelaksanaan Pembelajaran Jarak Jauh Masa Pandemi Coronavirus Disease 2019 (Covid-19) di MIN 1 Rembang - Shofaul Hikmah (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2020)
Coronaviruse Disease 2019 (Covid-19) makes teaching and learning to be carried out remotely, to protect the safety and health of students from the threat of Covid-19. MIN 1 Rembang as an institution under the Ministry of Religion utilizes a distance learning application launched by the Ministry of Religion, namely Madrasah E-learning. This study aims to describe Distance Learning using Madrasah E-Learning for MIN 1 Rembang students. This study used a qualitative research method with a descriptive qualitative design (case study). The data collection technique used an online questionnaire using Microsoft Form. The results showed that the Madrasah E-learning application proved to be useful as a learning technique during the 2019 Coronavirus Disease Pandemic (Covid-19). This can be seen from the results of the questionnaire given to respondents on average showing that Madrasah E-Learning can be the main means and choice for the implementation of teaching and learning activities for MIN 1 Rembang students during the current Coronavirus Disease 2019 (Covid-19) pandemic.